2020
DOI: 10.1038/s41598-020-76900-x
|View full text |Cite
|
Sign up to set email alerts
|

The dehydrins gene expression differs across ecotypes in Norway spruce and relates to weather fluctuations

Abstract: Norway spruce has a broad natural distribution range, which results in a substantial variety of its physiological and genetic variation. There are three distinct altitudinal ecotypes described in this tree species. The physiological optimum of each ecotype may be shifted due to ongoing climate change, especially in traits associated with water demand that might be crucial for adaptation. Dehydrins are proteins that help to mitigate the adverse effects of dehydration. Dehydrin gene expression patterns appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In a previous study (Ouyang et al, 2020), it was not clear if dehydrins reacted only to temperature or are also induced by SD. In Norway spruce, PaDHN6 was described to be regulated by temperatures but was also highly up-regulated by a short period of SD (Cepl et al, 2020). Here, we show that after 24 h SD at 20/18 • C (HT), RhDHN5 transcripts responded to a limited but significant effect for 'Yesterday', 'Abraham Darby', and R. wichurana (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…In a previous study (Ouyang et al, 2020), it was not clear if dehydrins reacted only to temperature or are also induced by SD. In Norway spruce, PaDHN6 was described to be regulated by temperatures but was also highly up-regulated by a short period of SD (Cepl et al, 2020). Here, we show that after 24 h SD at 20/18 • C (HT), RhDHN5 transcripts responded to a limited but significant effect for 'Yesterday', 'Abraham Darby', and R. wichurana (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…We assumed the adaptation to the original climatic conditions was genetically determined. These assumptions were supported by preliminary SNPs data cluster analysis ( Čepl et al, 2020 ). Although there is no information about distinguishing Norway spruce ecotypes from spectral reflectance neither at canopy nor at needle level, we expected these adaptations to be reflected in variable hyperspectral reflectance of young shoots.…”
Section: Discussionmentioning
confidence: 73%
“…High variation in drought stress within Norway spruce populations across vegetation zones was previously reported ( Trujillo-Moya et al, 2018 ). Recently, a significant variation among Norway spruce ecotypes was found in dehydrin gene expression ( Čepl et al, 2020 ). The most notable difference between acuminata and obovata ecotype was found in specific dehydrin PaCAP1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…As we focused on mature trees that persist on the stand despite the ontogenetic selection, we probably largely genotyped individuals that bear distinctive genetic pattern favorable to higher altitudes. Additionally, several ecophysiological studies indicated the resilient specific status of high-elevation ecotype such as enhanced drought tolerance 107 , higher nitrogenous content in needles 108 , and significantly different patterns in dehydrin gene expression 109 .…”
Section: Discussionmentioning
confidence: 99%